2016
DOI: 10.1167/16.8.2
|View full text |Cite
|
Sign up to set email alerts
|

The absolute disparity anomaly and the mechanism of relative disparities

Abstract: There has been a long-standing debate about the mechanisms underlying the perception of stereoscopic depth and the computation of the relative disparities that it relies on. Relative disparities between visual objects could be computed in two ways: (a) using the difference in the object's absolute disparities (Hypothesis 1) or (b) using relative disparities based on the differences in the monocular separations between objects (Hypothesis 2). To differentiate between these hypotheses, we measured stereoscopic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 54 publications
2
21
0
Order By: Relevance
“…The additional spheres were arranged in form of three rings (each constituted by 12 spheres) around the central target, with a radius of 18, 27, and 36 cm, respectively ( Figure 1 ). In general, relative depth information has been discussed to be an important source for depth perception (Neri et al, 2004; Chopin et al, 2016). Within a virtual 3D setting relative depth information has also been shown to be a prerequisite to detect RT effects (Plewan and Rinkenauer, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…The additional spheres were arranged in form of three rings (each constituted by 12 spheres) around the central target, with a radius of 18, 27, and 36 cm, respectively ( Figure 1 ). In general, relative depth information has been discussed to be an important source for depth perception (Neri et al, 2004; Chopin et al, 2016). Within a virtual 3D setting relative depth information has also been shown to be a prerequisite to detect RT effects (Plewan and Rinkenauer, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Relative disparity is the difference between the absolute disparities of two objects. There is converging evidence that relative disparities are calculated from absolute disparities and that the two systems are therefore not independent . However, conscious depth perception shows little or no direct access to absolute disparities (the absolute disparity anomaly).…”
Section: How To Measure Stereoacuity For Determining Stereoblindness?mentioning
confidence: 99%
“…There is converging evidence that relative disparities are calculated from absolute disparities and that the two systems are therefore not independent . However, conscious depth perception shows little or no direct access to absolute disparities (the absolute disparity anomaly). Some brain‐damaged patients can also show large impairments of stereopsis from relative disparities while still be able to normally (but poorly) access absolute disparities .…”
Section: How To Measure Stereoacuity For Determining Stereoblindness?mentioning
confidence: 99%
See 1 more Smart Citation
“…Slant from HSR is defined by a smooth disparity gradient. It has been found that slant is processed more accurately (Brookes & Stevens, 1989 ; Stevens & Brookes, 1988 ; van Ee et al, 1999 ; van Ee & Erkelens, 1995 ) and faster (Gillam, Chambers, & Russo, 1988 ; Gillam et al, 1984 ; van Ee & Erkelens, 1996 ) when a reference frame is provided, because across short distances within the visual field, relative disparity is measured very robustly (Backus & Matza-Brown, 2003 ; Blakemore, 1970 ; Chopin, Levi, Knill, & Bavelier, 2016 ).…”
Section: Experiments 4: Slant Contrastmentioning
confidence: 99%